Validation of Malay Beck Cognitive Insight Scale (BCIS) - Othman, Zahiruddin; Chong, Teck Lua (Japan International Cultural Exchange Foundation, 2017)
Background: Although the dominant current viewpoint of insight is related to clinical insight, cognitive insight has been gaining popularity since the introduction of Beck Cognitive Insight Scale (BCIS) in 2004. Therefore, an easy and reliable assessment tool of cognitive insight is needed to complement the assessment of clinical insight to improve the psychiatric services and outcomes. Objectives: This study aimed to validate the Malay Beck Cognitive Insight Scale (BCIS-M). Methods: The BCIS was translated into Malay language with good face and content validity. It was administered to 75 patients with schizophrenia in psychiatric outpatient clinic, Hospital Universiti Sains Malaysia (HUSM) in April 2014. Results: The BCIS-M showed good psychometric property. The internal consistency (Cronbach alpha) for self-certainty and self-reflectiveness in this study were 0.609 and 0.699, respectively. Conclusion: The BCIS-M is a valid and reliable tool for assessment of cognitive insight in local Malaysian population.